In vivo effect of pregnancy on angiogenesis potential of arteriovenous malformation tissue samples: an experimental study - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2017)
BACKGROUND: Increased angiogenic potential of cerebrovascular malformations during pregnancy may help to explain the complications of arteriovenous malformations (AVMs) in this group of patients. This experimental study investigated the effect of pregnancy on angiogenic activity of implanted AVM tissue samples. METHODS: A subject group of 10 pregnant rats and 10 non-pregnant rats as controls were used. Surgical AVM resection samples were implanted into the micropocket created in both eyes of each animal. Vascular development was assessed by vessel count throughout the study period. In addition, immunohistochemical studies were done for vascular endothelial growth factor (VEGF), platelet derived growth factor (PDGF), and their receptors (VEGFR, PDGFR). RESULTS: Statistically significant increase in the number of vessels was found in both groups (P<0.0001); however, the increase in the pregnant group was greater (P=0.0032). The difference between the two groups was evident at the 25th day of the experiment. Despite both groups showed increased level, there was no difference with the level of VEGF, VEGF receptor, PDGF, or PDGF receptor (P>0.05 for all comparisons). CONCLUSIONS: Findings of this study suggest that angiogenic activity of AVM tissues may increase during late pregnancy, hence physicians should inform pregnant patients with AVM of the potential risk.
Keywords: Arteriovenous malformations; Cornea; Pregnancy; Platelet-derived growth factor; Receptors, vascular endothelial growth factor; RAT CORNEA MODEL; ENDOVASCULAR TREATMENT; HEMORRHAGE; INHIBITION; ANEURYSMS